2022
DOI: 10.3390/life12010117
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering and Regeneration of the Human Hair Follicle in Androgenetic Alopecia: Literature Review

Abstract: Androgenetic alopecia (AGA) is an androgen-dependent process and represents the most frequent non-scarring alopecia. Treatments for AGA do not always achieve a satisfactory result for the patient, and sometimes cause side effects that lead to discontinuation of treatment. AGA therapeutics currently includes topical and oral drugs, as well as follicular unit micro-transplantation techniques. Tissue engineering (TE) is postulated as one of the possible future solutions to the problem and aims to develop fully fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Many researchers have cultured and studied DP cells (DPCs) to use for hair growth or generation of HFs. Researchers have shown that a hair structure can be created from stem cells and mice DPCs; however, this was unsuccessful in humans because of the loss of trichogenic ability and the poor functionality of the cultured human DPCs ( Ji et al, 2021 ; Llamas-Molina et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have cultured and studied DP cells (DPCs) to use for hair growth or generation of HFs. Researchers have shown that a hair structure can be created from stem cells and mice DPCs; however, this was unsuccessful in humans because of the loss of trichogenic ability and the poor functionality of the cultured human DPCs ( Ji et al, 2021 ; Llamas-Molina et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are tiny particles containing cytoplasmic components that are released by cells during cell growth and cell membrane fission 21 and are an important component of paracrine signaling. They regulate the biological activity of recipient cells and mediate intercellular communication, allowing cells to grow and communicate through proteins, nucleic acids, and lipids that carry 22 . It was found that in vitro induction induced proliferation and migration of human dermal papilla cells and secretion of VEGF and IGF‐1 23 .…”
Section: Discussionmentioning
confidence: 99%
“…They regulate the biological activity of recipient cells and mediate intercellular communication, allowing cells to grow and communicate through proteins, nucleic acids, and lipids that carry. 22 It was found that in vitro induction induced proliferation and migration of human dermal papilla cells and secretion of VEGF and IGF-1. 23 Exosomes of hypoxia-pretreated adipose mesenchymal stem cells (ADSCs)…”
Section: Discussionmentioning
confidence: 99%
“…The anagen stage begins with the development of HF, in which lower HF filaments are formed with the proliferation of secondary germ cells in the hair bulge 45,46 . In the human scalp, anagen lasts 1–6 years and involves complete regeneration of the circulating portion of the HF 47 . Melanocyte stem cells swell during anagen and are activated together with HFSCs to generate pigment granules and mature melanocytes that are distributed to adjacent differentiated cells to form coloured hair fibres 48 .…”
Section: Hair Follicle Cyclementioning
confidence: 99%
“…45,46 In the human scalp, anagen lasts 1-6 years and involves complete regeneration of the circulating portion of the HF. 47 Melanocyte stem cells swell during anagen and are activated together with HFSCs to generate pigment granules and mature melanocytes that are distributed to adjacent differentiated cells to form coloured hair fibres. 48 Catagen can persist for 4-6 weeks, during which keratinocytes and melanocytes undergo apoptosis, while DP migrates upwards undamaged until they are placed next to stem cells in the hair bulge.…”
Section: Hair Folli Cle C Yclementioning
confidence: 99%